Um estudo sobre a inter-relação de métodos projetuais na concepção de produtos futuros no desenvolvimento conceitual de veículo agrícola - Silva, Carlos Davi Matiuzzi da (2013)
In a market reality where the problems and variables are increasingly complex, the speed of processing and dissemination of information is accelerating day by day to the emergence of new products and products that we can not even think of them enjoy . It is said that these aspects there is a constant related companies increasingly consumerist and dependents o industrial artifacts manufactured. Thus, the diverse range of projects with which design professionals are faced today because the accumulation of experience is more fragmented before the variety of problems to be solved. These factors are crucial to justify the need to make use of well-structured design methods and flexible development of these activities. However, one can see that these methods are structured to provide a beginning, middle and end very clear to the activity, with a chain of tasks to be performed sequentially and logically. In PDPs linear as proposed by the Baxter (2010), Bonsiepe (1978), Rozenfeld et al. (2006) and Romano (2003) is not perceived clearly a pre-determined space for changes to be made and interference, even knowing that this is common practice both in academia and in the professional market, and the authors themselves admit that such interference should occur. These interferences must adapt these methods to the specific reality of each project modifying them to certain demands under certain focus and not pre-determined. These methods present various approaches and approaches while complementary. The purpose is thus interrelate methods through a systemic model of radial congruent steps projetuais and design tools to model MD3E proposed by Santos (2005), where all features of the design activity is complemented resulting in a conceptual design agricultural vehicle that pulled structure from is a future scenario. For the result is expected from a more flexible model it is possible to design professionals also be used tools related fields or even new tools projects thereby demonstrating better quality, innovative and less uncertainty. And due to this, fewer failures and more success in developing new products